Squatters and Politics in Montevideo at the Turn of the Century (2015)
This chapter analyzes the history of the informal city in Montevideo from a social movement perspective. It argues that, like other more structured social movements in the region, squatters were affected by neoliberal reforms and democratization in the past decades of the twentieth century. It focuses particularly on the role of two political opportunities stemming from democratization, namely electoral competition and decentralization. While the first one gave squatters influential allies, the second one opened institutional access for them. Yet, not all squatters were equally endowed to seize those opportunities. Those with more political networks, organizational experience, and better socioeconomic conditions were better able to use those opportunities to seize land, plan their neighborhoods, and get goods and services for them. Based on quantitative and qualitative data on land seizures and neighborhood histories, respectively, the article argues for an interactive theory of mobilization that considers both hardships and political factors to understand squatting.